(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article presents some attempts at denial or interrogation, which may raise the question: what (isn’t) autofiction? Considering that in the fields of research in education, language and theatricality, writing exercises are always crossed and linked to the bodies of their authors, the article defends the idea that autofiction in the academic universe wants and should be mobile, sliding, erroneous, unclassifiable and unpredictable, just like the bodies that write it. Without the intention of constituting itself as a panorama of studies in related areas, the work is of an essayistic-bibliographical nature and finds its main theoretical anchor in Bakhtin and the Circle.